PENERAPAN TEORI MULTIPLE INTELLIGENCES HOWARD GARDNER DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM - Mushollin, Mushollin (STAIN Pamekasan, 2009)
Abstract: This article is to describe the concept and the theory of Multiple Intelligences developd by Howard Gardner. Furthermore, it tries to explain how they are applied in the classroom in the Islamic education learning. The theory is the development of doubled-intelligences theory stating that human have different intelligences. Gardner argues that human are endowed eight intelligences—linguistic, natural, logic-mathematic, interpersonal, intrapersonal, spatial, musical, and natural. In educational context, Gardners theory effects the learning practice in school as well as the parents treatment to the children in the house. In practice, learning is demanded to develop each intelligence and use any kinds of intelligences to measure the students intelligence.